2019
DOI: 10.2196/12033
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Phone–Based Approach for Hearing Screening of School-Age Children: Cross-Sectional Validation Study

Abstract: Background Pure-tone screening (PTS) is considered as the gold standard for hearing screening programs in school-age children. Mobile devices, such as mobile phones, have the potential for audiometric testing. Objective This study aimed to demonstrate a new approach to rapidly screen hearing status and provide stratified test values, using a smartphone-based hearing screening app, for each screened ear of school-age children. Method This was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 40 publications
(74 reference statements)
1
34
1
3
Order By: Relevance
“…Since conventional pure-tone audiometry is mostly unavailable in PCP settings, innovative telehealth [14,40,42,43]. The Ear Scale app proposed in this study has been shown to be feasible for hearing screenings in the pediatric population [26] and has been shown to have a good level of diagnostic accuracy for SSNHL. We believe that this novel tool, which incorporates the HST and smartphone-based technology, can serve as a point-of-care test for SSNHL at the PCP level because it is affordable, efficient, and requires minimal training to administer.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Since conventional pure-tone audiometry is mostly unavailable in PCP settings, innovative telehealth [14,40,42,43]. The Ear Scale app proposed in this study has been shown to be feasible for hearing screenings in the pediatric population [26] and has been shown to have a good level of diagnostic accuracy for SSNHL. We believe that this novel tool, which incorporates the HST and smartphone-based technology, can serve as a point-of-care test for SSNHL at the PCP level because it is affordable, efficient, and requires minimal training to administer.…”
Section: Discussionmentioning
confidence: 98%
“…The adjacent scales differed from one another by 5 dB (Multimedia Appendix 1). The test tones lasted for 1.5 seconds, and the silent intervals lasted for 2 to 3 seconds [26,28]. The Ear Scale app started with hearing scale 5 (S5), which corresponded to 25 dB HL.…”
Section: Smartphone-based Hearing Screening Appmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of this literature probes the applicability of mobile hearing testing in young adults or children. The paper presented by [81] is a case in point, where the authors outline a smartphone-based hearing screening method. The authors explore and compare their proposed smartphone-based hearing screening app (Ear Scale app) with Pure-tone Screening (PTS) in a sound-treated booth to test the hearing of school-age children.…”
Section: Hearing Testing Using Smartphonesmentioning
confidence: 99%